A Giant with Feet of Clay? The EU’s Ability to Develop Capabilities for Civilian Crisis Management - Rafal Domisiewicz (Romanian Journal of European Affairs, 2012)
Civilian crisis management has long been considered the EU’s forte. Recent research however has questioned the EU’s claim to this specialization. I will interrogate how the EU has fared in building civilian capabilities for CSDP through a case study of the impact of the Europeanization of CCM norms in one of the newer EU member states - Poland. I investigate the domestic reverberations of an EU-level CCM governance – conceptualized as a vertical diffusion of norms - and a horizontal diffusion in the realms of policy setting, institutional adaptation, as well as in recruitment and training. I hypothesize that the European cognitive constructions and policy designs are the more likely to impact upon Polish security policy the more they resonate with the ideas embedded in the national security identity. Another intervening variable affecting the ‘translation’ of EU policy into the domestic context is state capacity. Due to weaknesses in the supply side of CCM and the refracting impact of national security identity and state capacity, I find that Europeanization has had a limited impact on the civilian response capability-building in Poland. Europeanization has been shallow, featuring adjustments on the margins rather than the core of the security policy.